RNA-Seq analysis reveals insight into enhanced rice Xa7-mediated bacterial blight resistance at high temperature - Cohen, Stephen P.; Liu, Hongxia; Argueso, Cristiana T.; Pereira, Andy; Vera Cruz, Casiana; Verdier, Valérie; Leach, Jan E. (Public Library of Science, 2017)
Plant disease is a major challenge to agriculture worldwide, and it is exacerbated by abiotic environmental factors. During some plant-pathogen interactions, heat stress allows pathogens to overcome host resistance, a phenomenon which could severely impact crop productivity considering the global warming trends associated with climate change. Despite the importance of this phenomenon, little is known about the underlying molecular mechanisms. To better understand host plant responses during simultaneous heat and pathogen stress, we conducted a transcriptomics experiment for rice plants (cultivar IRBB61) containing Xa7, a bacterial blight disease resistance (R) gene, that were infected with Xanthomonas oryzae, the bacterial blight pathogen of rice, during high temperature stress. Xa7-mediated resistance is unusual relative to resistance mediated by other R genes in that it functions better at high temperatures. Using RNA-Seq technology, we identified 8,499 differentially expressed genes as temperature responsive in rice cultivar IRBB61 experiencing susceptible and resistant interactions across three time points. Notably, genes in the plant hormone abscisic acid biosynthesis and response pathways were up-regulated by high temperature in both mock-treated plants and plants experiencing a susceptible interaction and were suppressed by high temperature in plants exhibiting Xa7-mediated resistance. Genes responsive to salicylic acid, an important plant hormone for disease resistance, were down-regulated by high temperature during both the susceptible and resistant interactions, suggesting that enhanced Xa7-mediated resistance at high temperature is not dependent on salicylic acid signaling. A DNA sequence motif similar to known abscisic acid-responsive cis-regulatory elements was identified in the promoter region upstream of genes up-regulated in susceptible but down-regulated in resistant interactions. The results of our study suggest that the plant hormone abscisic acid is an important node for cross-talk between plant transcriptional response pathways to high temperature stress and pathogen attack. Genes in this pathway represent an important focus for future study to determine how plants evolved to deal with simultaneous abiotic and biotic stresses